The Relationship Between Religion, Politics, and Social Change in Sustainable Development - Akdila Bulanov; Fanisa Mutiara; Wafiq Azizah; Siti Aisyah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Sustainable development is a complex process that focuses not only on economic growth but also involves spiritual, political, and social structural dimensions. This article aims to analyze the relationship between religion, politics, and social change in supporting inclusive and human-centered development. Religion acts as social capital and a moral driver that strengthens solidarity and work ethics. On the other hand, development politics functions as an instrument for the allocation of power that ideally transforms towards democratic consolidation ensuring social justice. Social changes triggered by development bring systemic impacts, ranging from economic modernization and urbanization to shifts in cultural values and gender roles. The results of the analysis indicate that the integration of non-doctrinaire religious values, participatory political policies, and the proper management of social change impacts are the key elements in achieving robust and sustainable community welfare.